Transport and deposition of nano-fibers in human upper tracheobronchial airways. (January 2016) - Tian, Lin; Ahmadi, Goodarz
Abstract: The elongated shape of the asbestos fibers makes them an extreme respiratory hazard as they can penetrate and deposit deep into the lung and could cause malignant pathological responses. Transport and deposition of these fibers are strongly affected by their diameter and aspect ratio, airflow condition, and the airway morphology. Compared to spherical particles, motions of elongated fibers are more complex due to the coupling between their translational and rotational movements. Very few prior works resolved the full motion of nano-scale fibers where the Brownian diffusion is dominant. In this work, the transport and deposition of nano-fibers were numerically simulated in a physiologically realistic lung bifurcation model. Detailed motion of the inhaled nano-fibers and their interactions with the surrounding environment were reproduced by solving a system of coupled nonlinear equations governing the translational and rotational motions. Hydrodynamic drag and torque, turbulence dispersion, gravitational sedimentation, and the Brownian diffusion were accounted for. Correlations of these forces with the fiber transport and deposition pattern, fiber characteristics, human breathing condition, and airway morphology were analyzed. The study uncovered the very important role of Brownian dynamics in the motion of the nano-fibers in human tracheobronchial airways, which can help explain many of the earlier experimental findings. The simulation results were compared with the experimental measurements, and the carcinogenicity of these fibers in human airways was discussed. Highlights: The transport and deposition of nano-fibers were numerically simulated in a physiologically realistic lung bifurcation model. Detailed motion of the inhaled fibers and their interaction with the surrounding environment were reproduced by solving a system of coupled nonlinear equations governing the fibers׳ translational and rotational motions. The study uncovered the very important role of Brownian dynamics in the motion of thin fibers in human tracheobronchial airways, which can help explain many of the earlier experimental findings.